Optimal Two Dimensional Preventive Maintenance Policy Based on Asymmetric Copula Function - Xinyue Li; Yunxian Jia; Zhen Li (Universitas Ahmad Dahlan, 2015)
For some kinds of products, the consumers have strict requirements to the reliability of these products in the based warranty period. Then the manufacturer is inclined to provide the two-dimensional preventive maintenance policy to take the usage degree of the product into account. As a result, two-dimensional preventive maintenance policy in the warranty period has recently obtained increasing attention from manufacturers and consumers. In this paper, we focused on the optimization of based warranty cost and proposed a new expected based warranty cost model considering the two-dimensional imperfect preventive maintenance policy from the perspective of the manufacture. Asymmetric copula function was applied to modeling the failure function of the product. And the optimal two-dimensional preventive maintenance period was obtained by minimizing based warranty cost. At last, numerical examples are given to illustrate the proposed models, of which the results prove the model effective and validate.